2020
DOI: 10.1042/bsr20191557
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic adnexal carcinoma: report of rare cases

Abstract: Microcystic adnexal carcinoma (MAC) is a rare, locally aggressive malignant neoplasm that derives from cutaneous eccrine/apocrine glands. MAC is classified as an eccrine/apocrine gland tumor and usually occurs in the skin. Here, we characterized and compared two cases of MAC. One is extremely rare in terms of its occurrence in the tongue. The other occurred in the lip, which is common. Histories of disease, diagnosis, and differentials were reviewed by the attending physicians. Hematoxylin and Eosin (HE) slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Sclerosing microcystic adenocarcinoma (SMA) is a unique minor salivary gland neoplasm primarily affecting individuals with a mean age of 56 years and apparent female predominance (F/M: 9/5) ( 4 , 5 ). A few reports of extracutaneous head and neck MAC in the tongue and parotid gland were published in 1995 ( 1 , 6 ). Anne M et al in 2016 reported five patients with MAC-like tumors arising in the mucosal surfaces of the head and neck ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sclerosing microcystic adenocarcinoma (SMA) is a unique minor salivary gland neoplasm primarily affecting individuals with a mean age of 56 years and apparent female predominance (F/M: 9/5) ( 4 , 5 ). A few reports of extracutaneous head and neck MAC in the tongue and parotid gland were published in 1995 ( 1 , 6 ). Anne M et al in 2016 reported five patients with MAC-like tumors arising in the mucosal surfaces of the head and neck ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“… [13] 55 F Floor of mouth CT Excision and adjuvant radiotherapy Disease free (10) 17 Zhang et al. [14] 51 M Tongue Not stated Excision Disease free (38) 18 Jiang et al. [15] 41 F Tongue Not stated Excision Not stated 19 Tan et al.…”
Section: Discussionmentioning
confidence: 99%
“…proposed the term “sclerosing microcystic adenocarcinoma (SMA)” for a rare malignant tumor occurring in the salivary glands, closely resembling cutaneous MAC [11] . To our knowledge, 21 cases of SMA have been reported, but none have evaluated the magnetic resonance imaging (MRI) findings of SMA in detail [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Here, we report an additional case of SMA of the floor of the mouth and discuss its MRI findings.…”
Section: Introductionmentioning
confidence: 99%
“…[4] MAC is a benign appearing lesion that often presents as an asymptomatic, slow-growing, indurated, flesh-colored to yellowish nodule, plaque on the central face area, commonly the upper lip, and nasolabial folds. [5] Histologically, MAC is characterized by follicular and sweat gland differentiation and overall benign features; however, it exhibits locally aggressive behavior that typically extends a few centimeters beyond the clinically visible margins, and usually infiltrates deeply into the muscle, cartilage, bone, and nerves. [6] Perineural invasion was commonly seen in MAC and often leads to local recurrence.…”
Section: Introductionmentioning
confidence: 99%